Beet Root Juice: An Ergogenic Aid for Exercise and the Aging Brain. (9th November 2016) - Petrie, Meredith; Rejeski, W. Jack; Basu, Swati; Laurienti, Paul J; Marsh, Anthony P; Norris, James L; Kim-Shapiro, Daniel B; Burdette, Jonathan H
Abstract: Background: Exercise has positive neuroplastic effects on the aging brain. It has also been shown that ingestion of beet root juice (BRJ) increases blood flow to the brain and enhances exercise performance. Here, we examined whether there are synergistic effects of BRJ and exercise on neuroplasticity in the aging brain. Methods: Peak metabolic equivalent (MET) capacity and resting-state magnetic resonance imaging functional brain network organization are reported on 26 older (mean age = 65.4 years) participants randomly assigned to 6 weeks of exercise + BRJ or exercise + placebo. Results: Somatomotor community structure consistency was significantly enhanced in the exercise + BRJ group following the intervention ( M BRJ = −2.27, SE = 0.145, M Placebo = −2.89, SE = 0.156, p = .007). Differences in second-order connections between the somatomotor cortex and insular cortex were also significant; the exercise + BRJ group ( M = 3.28, SE = 0.167) had a significantly lower number of connections than exercise + placebo ( M = 3.91, SE = 0.18, p = .017) following the intervention. Evaluation of peak MET capacity revealed a trend for the exercise + BRJ group to have higher MET capacity following the intervention. Conclusions: Older adults who exercised and consumed BRJ demonstrated greater consistency within the motor community and fewer secondary connections with the insular cortex compared with those who exercised without BRJ. The exercise + BRJ group had brain networks that more closely resembled those of younger adults, showing the potential enhanced neuroplasticity conferred by combining exercise and BRJ consumption.